Pemberdayaan Masyarakat Berbasis Nilai-Nilai Islam melalui Pendekatan Ilmu Pengembangan Masyarakat Islam - Asmaria; Zesty Miranda (ABDI AKOMMEDIA : JURNAL PENGABDIAN MASYARAKAT, 2025)
This community service activity aims to empower communities based on Islamic values through the approach of Islamic Community Development. Community empowerment is an important strategy to address social, economic, and spiritual problems faced by Muslim communities, especially in rural areas. This program was implemented using a participatory approach with the Participatory Action Research (PAR) method, which involves the community actively in all stages of the activity, including problem identification, program planning, implementation, and evaluation. The activities carried out included strengthening religious awareness through thematic Islamic studies, enhancing social participation, mentoring productive economic activities based on local potential, and strengthening mosque-based social institutions. The results of the community service showed positive changes, including increased religious awareness, stronger social solidarity, higher community participation, and improved understanding of Islamic-based economic empowerment. Supporting factors for the success of this program included active community involvement, support from religious and community leaders, and the utilization of religious institutions as empowerment centers. Meanwhile, the main obstacles encountered were limited mentoring time and resource constraints. Overall, the Islamic Community Development approach proved effective in creating holistic and sustainable community empowerment.